2014
DOI: 10.1002/chin.201425145
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of 2‐Tetrazolylmethyl‐2,3,4,9‐tetrahydro‐1H‐β‐carbolines by a One‐Pot Ugi‐Azide/Pictet—Spengler Process.

Abstract: Synthesis of 2-Tetrazolylmethyl-2,3,4,9-tetrahydro-1H--carbolines by a One-Pot Ugi-Azide/Pictet-Spengler Process. -(CARDENAS-GALINDO, L. E.; ISLAS-JACOME, A.; ALVAREZ-RODRIGUEZ, N. V.; EL KAIM, L.; GAMEZ-MONTANO*, R.; Synthesis 46 (2014) 1, 49-56, http://dx.doi.org/10.1055/s-0033-1340051 ; Fac. Quim., Univ. Guanajuato, 36050 Guanajuato, Mex.; Eng.) -M. Tismer 25-145

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In 2014, El Kaim and Gámez-Montaño reported an efficient Pictet–Spengler reaction of Ugi-azide adducts and formaldehyde ( Scheme 22 ). Under microwave heating, a series of 2-tetrazolylmethyl-2,3,4,9-tetrahydro1H-β-carbolines was synthesized in 73–83% yield in 5 h, while conventional heating gave 74–86% yield in 72 h, indicating that microwave irradiation remarkably shortens the reaction time of this transition metal-free process [ 26 ].…”
Section: Transition Metal-free Catalysismentioning
confidence: 99%
“…In 2014, El Kaim and Gámez-Montaño reported an efficient Pictet–Spengler reaction of Ugi-azide adducts and formaldehyde ( Scheme 22 ). Under microwave heating, a series of 2-tetrazolylmethyl-2,3,4,9-tetrahydro1H-β-carbolines was synthesized in 73–83% yield in 5 h, while conventional heating gave 74–86% yield in 72 h, indicating that microwave irradiation remarkably shortens the reaction time of this transition metal-free process [ 26 ].…”
Section: Transition Metal-free Catalysismentioning
confidence: 99%
“…As a part of our research, we recently reported the synthesis of bis-heterocycles via the two efficient I-MCR strategies: the Ugi-Azide (UA) [18][19][20][21][22][23][24] and the Groebke-Blackburn-Bienaymé (GBB) reactions [25][26][27]. The combination of I-MCRs with efficient post-transformation processes like annulation [21,22] or cascade process [23,24] improve their synthetic potency.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of I-MCRs with efficient post-transformation processes like annulation [21,22] or cascade process [23,24] improve their synthetic potency.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, based on our ongoing efforts in the development of short and versatile methodologies toward the synthesis of tetrazole-containing hybrid compounds having frameworks of interest in medicinal chemistry, such as terazol-chromones [12], tetrazol-tetrahydro-β-1H-carbolines [13] and tetrazol-azepinoindolones [14], we herein report the synthesis of a series of five novel bis-1,5-DS-1H-T 15a-e using a catalyst-free Ugi-azide repetitive process. …”
Section: Introductionmentioning
confidence: 99%